2019
DOI: 10.3390/app9163417
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Method for Angular Positioning Deviation of a High-Precision Rotary Table Based on the Laser Tracer Multi-Station Measurement System

Abstract: This paper proposes a calibration method for angular positioning deviation of a high-precision rotary table based on the laser tracer multi-station measurement system. The algorithm error of the calibration method for angular positioning deviation of a high-precision rotary table based on the laser tracer multi-station measurement system was mainly discussed. During the experiments, the laser tracer was fixed on the work surface of the rotary table, and the rotary was fixed on the work surface of the coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Mishra, Pandey, and Saripalli (2020) presented a method, which uses the data collected by flat plates placed in different postures in the common field of view of LiDAR and camera, then a function model is established according to geometric constraints, and the LiDAR-Camera system is calibrated using non-linear least squares. Chen et al (2019) used a method based on the laser tracer multistation measurement system to calibrate the angular positioning deviation of a high-precision rotary table; according to their experimental results, the angular positioning deviation of the high-precision rotary table was as low as ±0.9", and the error of the calibration method was ±0.4".…”
Section: Overview Methodologymentioning
confidence: 99%
“…Mishra, Pandey, and Saripalli (2020) presented a method, which uses the data collected by flat plates placed in different postures in the common field of view of LiDAR and camera, then a function model is established according to geometric constraints, and the LiDAR-Camera system is calibrated using non-linear least squares. Chen et al (2019) used a method based on the laser tracer multistation measurement system to calibrate the angular positioning deviation of a high-precision rotary table; according to their experimental results, the angular positioning deviation of the high-precision rotary table was as low as ±0.9", and the error of the calibration method was ±0.4".…”
Section: Overview Methodologymentioning
confidence: 99%
“…The ball plate artifacts contained seven balls or twelve balls. Previous studies indicated that six parametric errors could be measured using a commercial instrument, LaserTRACER [29][30][31] or Laser Tracker [32]. This method placed the commercial instrument in four spatial positions.…”
Section: Introductionmentioning
confidence: 99%
“…Influences under this point will affect the result in reality. In 2019, H. Chen [18] introduced a multi-station measurement system using a laser tracer applied on large high-precision rotary tables; however, the system faces concentricity problems between the laser tracer and the rotary table. In 2021, D. Ma [19] executed a new measurement method as an independent system for all motion errors of a rotary axis based on a polyhedral prism.…”
Section: Introductionmentioning
confidence: 99%